Knowledge and predictors of retention of postpartum intrauterine contraceptive device among users in rural areas of Nadia district, West Bengal, India - Sharma, Jitu; Pal, Jayita (International Journal Of Community Medicine And Public Health, 2019)
Background: Postpartum intrauterine contraceptive device (PPIUCD) is a safe, highly effective postpartum contraceptive, yet to be popularized at the community level in a diversified developing country like India where still the unmet need for spacing remains high. This study aimed to assess the knowledge regarding PPIUCD among users and the predictors of its retention. Methods: A case-control study had been conducted using multi-stage sampling technique in Nadia district of West Bengal. Face to face interviews of the cases and the controls had been done with the help of a predesigned pretested semi-structured schedule. Data were entered in MS Excel and analysed in SPSS 20.0 version. Results: Majority of the acceptors (55.2%) had poor knowledge regarding PPIUCD. Most of the participants (62.2%) retained their PPIUCD at least for 6 months. Acceptors who belonged to Hindu religion, higher socio-economic class (I and II), nuclear family, educated up to or above secondary level, ever counselled on PPIUCD, satisfied using that in day to day life, undergone follow-up visits and had correct knowledge regarding different aspects of PPIUCD had higher odds of retention of PPIUCD. Conclusions: Regular awareness campaigns, counselling at household level, advocacy are the utmost needs of the hour to motivate the eligible couple for its acceptance and retention.